Cancellous Bone Mechanical Characterization and Finite Element Simulation - Syahrom, Ardiyansyah (Advanced Structured Materials,, 2018)
This book provides comprehensive mechanobiological insights into bone, including the microstructure of cancellous bone and its realistic loading in the human body. This approach considers different types of loads, i.e. static and dynamic, and the response under uniaxial and multiaxial loading conditions. The book also reviews additional factors influencing biomechanical properties, e.g. fluid transport. In closing, the mechanobiological approach is discussed in the context of the finite element method.